Efficient and sustainable conversion of CO₂ and propylene oxide to propylene carbonate using MgO-enhanced MgCo₂O₄ heterostructure catalyst - Tahani Saad Algarni; Naaser A. Y. Abduh; Saad Mohammed Alqahtani (Journal of Saudi Chemical Society)
Abstract Harnessing CO2 as a feedstock for producing value-added materials is recognized as a promising approach in sustainable chemistry. The significance of CO2 in synthesizing propylene carbonate (PC) through its coupling with propylene oxide (PO) is underscored by the diverse industrial applications of PC. To develop an effective Co-based spinel catalyst for PC production, spinel-type mixed metal oxides, MCo2O4 (M = Mg, Cu, Ni, Zn), were synthesized via a facile coprecipitation process. The high purity and well-defined cubic spinel structures of the materials were confirmed through X-ray diffraction (XRD) analysis. The catalytic performance of these oxides was evaluated for solvent-free PC production, with notable potential exhibited by MgCo2O4. The catalytic activity was enhanced by the development of a heterostructure catalyst of MgO/MgCo₂O₄. Various characterization techniques, including XRD, FTIR, XPS, BET, SEM, TEM, EDX, and TGA, were employed to assess the purity and structural features of the MgO/MgCo₂O₄ composite. Catalytic tests were conducted under mild conditions, with variations in cocatalyst type, reaction temperature, and CO2 pressure systematically introduced. The MgO/MgCo₂O₄ composite, with tetraethylammonium bromide (TEABr) used as a cocatalyst, achieved a PO conversion of 95% and a PC selectivity of 99% at 75 °C and 50 psi CO2 over six hours. The enhanced activity of MgCo2O4, supported by MgO, was linked to altered acid–base properties and improved particle dispersion. Additionally, the MgO/MgCo₂O₄ heterostructure catalyst exhibited good stability and could be recycled multiple times for PC synthesis without significant loss of performance. Graphical Abstract Graphical abstract of the preparation method and catalytic process.